Predictive accuracy of the Braden Q Scale in risk assessment for paediatric pressure ulcer: A meta-analysis - Yaoji Liao; Guozhen Gao; Lulu Mo (Elsevier, 2018)
Aims: Paediatric pressure ulcers are a serious problem to healthcare service. Thus, effective and early identification of the risk of developing pressure ulcer is essential. The Braden Q scale is a widely used tool in the risk assessment of paediatric pressure ulcer, but its predictive power is controversial. Hence, we performed a meta-analysis to evaluate the predictive power of the Braden Q scale for pressure ulcer in hospitalised children and offer recommendations for clinical decision. Methods: Studies that evaluated the predictive power of the Braden Q scale were searched through databases in English and Chinese, including Medline, Cochrane Library, Embase, CINAHL, SinoMed, CNKI, Wangfang and VIP. The studies were screened by two independent reviewers. QUADAS-2 was used to assess the risk of bias of eligible studies. Demographic data and predictive value indices were extracted. The pooled sensitivity, specificity and receiver operating characteristics (ROC) were calculated by MetaDiSc 1.4 using random-effects models. Results: Cochran Q = 26.13 (P = 0.0036) indicated the existence of heterogeneity; the I2 for pooled DOR was 61.7%, suggesting significant heterogeneity among the included studies. The pooled sensitivity and specificity were 0.73 (95% CI: 0.67-0.78) and 0.61 (95% CI: 0. 59-0.63), respectively, yielding a combined DOR of 3.47 (95% CI: 2-6.01). The area under the ROC curve was 0.7078 ± 0.0421, and the overall diagnostic accuracy (Q*) was 0.6591 ± 0.0337. Sensitivity analysis showed the results were robust. Conclusion: The Braden Q scale has moderate predictive validity with medium sensitivity and low specificity for pressure ulcers in hospitalised children. Further development and modification of this tool for use in paediatric population are warranted. Keywords: Braden Q scale, Child, Pressure injury, Pressure ulcer, Risk assessment, Sensitivity and specificity